Obtención de aceite refinado a partir de los desechos de pescado procedentes del Puerto Eduardo – Iquitos - Llerena Vela, Amador (2024)
The use and transformation of by-products from the fishing industry for efficient use of these natural resources helps mitigate the environmental impact. The waste studied from Puerto Eduardo is Mota (Calophysus macropterus L.) and Llambina (Potamorhina altamazonica). The objective of this research is to evaluate and determine the performance of obtaining refined oil from fish waste from the Eduardo – Iquitos port. A quantitative, correlational and experimental research was carried out. Concluding that the treatment of fish waste, based on the unit operations with which we work, significantly influences the performance of obtaining refined oil, with a correlation and determination coefficient (r = 0.999 and R2 = 0.999). The average amount of waste is 1512.65 with the oil extraction yield being 17.11%. With respect to the predominance of Mota (Calophysus macropterus L.) they are: density, acidity index, degree of acidity and saponification index, with respect to the predominance of Llambina (Potamorhina altamazonica) they are: humidity, peroxide index and molecular weight. The average physicochemical characteristics are: 0.035% humidity, 0.9128 g/mL density, 6.48 mg KOH/g fat acid value, 10.07% oleic acid acid value, 107.21 mEq O2/kg oil peroxide value, 411.68 mg KOH/ g of oil saponification index, and 414.72 g/mol molecular weight.